Enlargement of the Pancreas in Children Diagnosed with Acute Pancreatitis: An Approach Based on P/V Ratio - Raut, Dhanraj S.; Desai, Shubhangi A.; Raje, Dhananjay V.; Singh, Dinesh; Dandge, Vithalrao P. (Indian Journal of Radiology and Imaging, 2022)
Background Acute pancreatitis is a reversible inflammation of the pancreatic parenchyma. Enlargement of the pancreas is often envisaged in such conditions. This study evaluates P/V ratio, as a marker to decide pancreatic enlargement in disease condition.Purpose The aim of this study was to develop imaging-based diagnostic criterion for acute pancreatitis in children based on P/V ratio.Material and Methods This study included 37 children with acute pancreatitis and 283 children asymptomatic for pancreatic disorders, from a single hospital center. The age of children ranged between 2 and 18 years. P/V ratio, which is the ratio of greatest anteroposterior dimension of the head, body, and tail of the pancreas relative to the transverse lumbar vertebral body, was obtained for each child through ultrasonographic examination. Age-adjusted receiver operating characteristics (AROC) analysis was performed on P/V ratio at presentation for each pancreatic region, and the sensitivity at 90% specificity, the threshold errors, and the corresponding cutoffs were obtained. The enlargement assessment was also done after clinical recovery by referring to the cutoffs of respective regions.Results AROC analysis for males and females resulted into a maximum sensitivity of 83.33 and 81.67%, respectively, at 90% specificity for head. The error thresholds for both the groups were same, i.e., 0.098, indicating that 90% of the observations had errors less than the threshold. The corresponding P/V ratio cutoff for males and females was 0.43 and 0.42, respectively.Conclusion Radiologists and clinicians can refer a cutoff value of 0.4 for each region, along with hypoechogenicity, to decide about enlargement of the pancreas in acute pancreatitis condition.
Keywords: acute pancreatitis; acute recurrent pancreatitis; age-adjusted receiver operating characteristics; anteroposterior